2011
DOI: 10.1111/j.1471-0528.2011.03021.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and impact of cardiotocography training programmes: a systematic review

Abstract: Background The interpretation and management of cardiotocography (CTG) tracings are often criticised in obstetric malpractice cases. As a consequence, regular CTG training has been recommended, even though little is known about the effect of CTG training.Objectives To perform a systematic review of the existing literature on studies on CTG training in order to assess educational strategies, evaluation of training programmes, and impact of training programmes.Search strategy The Medline database was searched to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 32 publications
5
47
1
1
Order By: Relevance
“…comm.). A systematic review of educational strategies suggests that interpretive skills do improve after training . In contrast, in a previous study, we found no improvement in the proportion of individuals who classified CTGs correctly after the completion of the program, possibly reducing the incentive to implement the education program .…”
Section: Discussioncontrasting
confidence: 98%
“…comm.). A systematic review of educational strategies suggests that interpretive skills do improve after training . In contrast, in a previous study, we found no improvement in the proportion of individuals who classified CTGs correctly after the completion of the program, possibly reducing the incentive to implement the education program .…”
Section: Discussioncontrasting
confidence: 98%
“…Dekert et al (2010) hold that practical training improves learning and increases selfconfidence. Pehrson et al (2011) found that training can improve knowledge of cardiotocography (CTG), leading to better quality care. Team training courses (Beasley, 2005) improve the maternity team's knowledge and practical skills, resulting in greater structure in acute situations as well as security.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestions for improvement in CTG education have been proposed to overcome human errors in CTG management with the hope that improvements in neonatal outcomes would ensue . Although several studies conclude that CTG education leads to improved CTG knowledge and interpretation skills, few studies have evaluated the concomitant effect on neonatal outcomes and the results of these studies diverge …”
Section: Introductionmentioning
confidence: 99%